Impedance Characterization of DNA-functionalization Layers on AlGaN/GaN High Electron Mobility Transistors. (2015) - Espinosa, N.; Schwarz, S.U.; Cimalla, V.; Podolska, A.; Ambacher, O.
Abstract: Characterization and optimization for biosensor implementation with open gate AlGaN/GaN transistors is described. Probe-DNA was immobilized on the gate. As target, complementary DNA at 10 -12 - 10 -7 mol/L was added. To investigate the impedimetric properties of the sensing area, electrochemical impedance spectroscopy was used. For very low frequencies, the bio-functionalization layer was modeled as a membrane with a charge transfer resistor in series with a Warburg element. This component presents impedance to diffusion of electrolyte ions. Its behavior is intermediate between a capacitor and a resistor (membrane impedance). After probe-target matching, the charge transfer resistance and Warburg impedance were increased (lower flow of electrolyte ions through the membrane). Using this working principle, a dynamic detection of targets is proposed.